Biosynthesis of Silver Nanoparticles with Antifungal Potential - Firdous, Sayeed Mohammed; Das Kirtania, Moumita; Barik, Anwesha; Nayak, Amit Kumar; Dey, Sanjay (Current Nanomedicine, 2024)
Metallic nanoparticles, specifically silver nanoparticles, find huge applications in health, medicine, and drug delivery. However, the physical and chemical synthesis methods pose challenges regarding gener, action of toxic by-products, or high energy requirements. Hence biosynthetic approaches have gained interest in the last few years utilizing various sources including yeast, fungi, bacteria, or plant extracts containing reducing and capping agents like quercetin, apocyanin, gallic acid, alkaloids, tannins, <span class=
Keywords: plant extract and phytochemicals